Crop Depredation around Jaldapara Snctuary by Rhinoceros unicornis an Indicative Trend - Ghosh, Deepak K. (Indian Forester, 1996)
Crop depredation by Rhinoceros unicornis differs in nature from other animals. Feeding habits of this Perrissodactyla with a capability of extensive lower tract fermentation, enables it to synthesize microbial protein from nonprotein nitrogen, synthesize vitamina and detoxify many secondary plant compounds replenishing of which is done by adding high levebl of grains, to its fibrous diet, by "Crop Raiding".